Feminist judgments : rewritten criminal law opinions - Capers, Bennett, 1966-; Deer, Sarah, 1972-; Yung, Corey Rayburn, 1974- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
'Is it possible to be both a judge and a feminist?' Feminist Judgments: Rewritten Criminal Law Opinions answers that question in the affirmative by re-writing seminal opinions that implicate critical dimensions of criminal law jurisprudence, from the sexual assault law to provocation to cultural defences to the death penalty. Right now, one in three Americans has a criminal record, mass incarceration and over-criminalization are the norm, and our jails cycle through about ten million people each year. At the same time, sexual assaults are rarely prosecuted at all, domestic violence remains pervasive, and the distribution of punishment, and by extension justice, seems not only raced and classed, but also gendered. We have had #MeToo campaigns and #SayHerName campaigns, and yet not enough has changed. How might all of justice look different through a feminist lens. This book answers that question.
McQuirter v. State -- People v. Berry -- Coker v. Georgia -- Oliphant v. Suquamish Indian Tribe -- State v. Rusk -- People v. Wu -- Winnebago Tribe of Nebraska v. Bigfire -- Commonwealth v. Blache -- State v. Williams -- State v. Walden -- State v. Norman -- Whitner v. State -- United States v. Nwoye -- Erotic Services Provider Legal Education and Research Project v. Gascon.
Title from publisher's bibliographic system (viewed on 05 Dec 2022).
Keywords: Criminal law -- United States; Feminist jurisprudence -- United States